Implementation and Outcomes of Lay Health Worker–Led Self-Management Interventions for Long-Term Conditions and Prevention: A Systematic Review. (December 2019) - Punna, Mari; Kettunen, Tarja; Bagnall, Anne-Marie; Kasila, Kirsti
The aim of this study was to systematically review lay health worker (LHW)–led self-management interventions for adults with long-term conditions to see how the interventions have been implemented and to compose a synthesis of research findings, taking into consideration the intervention components that have been applied. We conducted systematic searches for articles published between January 2010 and December 2015 in five databases: Cochrane, MEDLINE, CINAHL, PsycINFO, and Web of Science. Forty original studies were found that met the inclusion criteria: self-management with diabetes ( n = 29), cardiovascular diseases ( n = 8), and those at risk of cardiovascular diseases ( n = 3). These consisted of 22 randomized controlled trials and 18 other trials, with durations of 1 day to 24 months. The findings showed that the training of LHWs and the implementation of interventions varied widely. A synthesis of the implementation methods covers the background of the LHWs and the interventions as well as the components applied in each. Eight interventions had effects on physical activity and eight on nutrition behavior. The review also includes preliminary findings on intervention components effective in improving physical activity and nutrition behavior, including self-monitoring as a behavior change technique and group meetings as an intervention format. The same components and behavior change techniques were applied in effective and noneffective interventions. The review found that LHW-led interventions have potential in promoting self-management in long-term condition. In the future, a qualified and evidence-based structure for LHW-led interventions is suggested in order to improve the systematization of interventions and their effects.